Authors and Academics: The Epistemic Culture of Linguistic Science Writing in Early American Grammars of Pacific Languages - Espree-Conaway, DeAndre (International Journal of Linguistics and Translation Studies, 2025)
This study examines four linguistic grammars published between 1905-1918, representing five Pacific languages—Rapa Nui (Easter Island), Tagalog (Philippines), Sissano (Papua New Guinea), Sa’a (Solomon Islands), and Ulawa (Solomon Islands)—in order to understand the linguistic practices of the epistemic culture that early linguistic science embodied. What was the culture of knowledge that governed the language of the authors of linguistic description while also itself being governed by it? In order to bring to light a response, this analysis relies on the theory of ‘discourses’ from Foucault’s work, The Archaeology of Knowledge and the methodology of Foucauldian Discourse Analysis derived from his work. In answering this question, it becomes necessary to understand what discourses are involved within the knowledge culture of early language science. Within this analysis, the study investigates the discursive constructions, discourses, action orientations, positionings, practices, and subjectivities involved in this epistemic culture. The conclusions of the analysis suggest that the epistemic culture of early linguistics was one of ‘representation by quantification,’ which legitimized the effects of imperialism through universals in a Euro-American-created historical universe.